2022
DOI: 10.1021/acs.biomac.2c01135
|View full text |Cite
|
Sign up to set email alerts
|

Poly(pro-curcumin) Materials Exhibit Dual Release Rates and Prolonged Antioxidant Activity as Thin Films and Self-Assembled Particles

Abstract: Curcumin is a natural polyphenol that exhibits remarkable antioxidant and anti-inflammatory activities; however, its clinical application is limited in part by its physiological instability. Here, we report the synthesis of curcumin-derived polyesters that release curcumin upon hydrolytic degradation to improve curcumin stability and solubility in physiological conditions. Curcumin was incorporated in the polymer backbone by a one-pot condensation polymerization in the presence of sebacoyl chloride and polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Through hydrolytic degradation followed by decarboxylation, we expect that cleavage of the urethane linkages will result in the release of curcumin, as well as the known auto-oxidation byproducts of curcumin. In addition, byproducts include PEG and the diaminotoluene derived from the TDI linker unit. At the same time, it has been shown that the curcumin within intact (not degraded) repeating units can still exert antioxidant activity, such that degradation is not a strict prerequisite for activity of the coated films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through hydrolytic degradation followed by decarboxylation, we expect that cleavage of the urethane linkages will result in the release of curcumin, as well as the known auto-oxidation byproducts of curcumin. In addition, byproducts include PEG and the diaminotoluene derived from the TDI linker unit. At the same time, it has been shown that the curcumin within intact (not degraded) repeating units can still exert antioxidant activity, such that degradation is not a strict prerequisite for activity of the coated films.…”
Section: Resultsmentioning
confidence: 99%
“…Different polymer architectures may also be assessed, such as dendrimers, to see if curcumin loading efficiency could be increased . Furthermore, future studies may consider using alternative linkers and copolymers to further improve biocompatibility; for example, a recent study in our lab used a sebacoyl linker in place of toluene diisocyanate . In addition to the incorporation of curcumin, future studies may also incorporate other small molecule anti-inflammatory agents to better target the macrophage and microglia response; for example, research has shown that Itgam, Cd14, and Irak4 play a major role in the innate immune response to electrode implantation and are potential targets for electrode coatings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradable polymers are emerging as important components in tissue engineering, bone repair, nano-vehicles for therapeutics drugs and genes in cancer treatment, and so forth. Among various chemical linkages that are readily susceptible to biodegradation under physiological conditions, aliphatic polyesters are very special due to their unique ability to degrade by lysosomal enzyme stimuli at the intracellular compartments. Aliphatic polyesters are typically synthesized either by ring opening polymerization (ROP) of cyclic monomers , or direct polycondensation of dicarboxylic acids and diols. , The ROP strategy has been used industrially for the production of polycaprolactone (PCL), poly­( l -lactic acid) and poly­( d , l -lactic- co -glycolic acid), and their di- and tri-block copolymers. , In the last decade, significant efforts have been taken to enhance the hydrolytic and environmental stability of the PLLA . Attempts have also been made to overcome the slow enzymatic biodegradation of PCL chains by functionalization of various side chains for drug delivery in cancer and antimicrobial agents. , On the contrary, the polycondensation approach for aliphatic polyesters has had limited success in commercial exploration due to poor mechanical properties, low molecular weights, limited enzymatic or microbial biodegradation, and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…Later on, several scientists developed methods for high yield synthesis of curcumin which are in use today . Curcumin is the most widely used plant-based drug with various pharmacological benefits, including anti-inflammatory, antioxidant, anti-viral, anti-bacterial, anti-fungal, anti-parasite, and anti-cancer. Numerous preclinical studies have proven curcumin to be effective in several cancers because of curcumin’s capability to induce G2/M cell cycle arrest, trigger apoptosis, induce autophagy, disturb molecular signaling, inhibit invasion and metastasis, and increase the efficiency of existing chemotherapeutics. , The inflammatory response of curcumin is often steered by the radical production of pro-inflammatory cytokines, including interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). , Consequently, the downregulation of pro-inflammatory cytokines may effectively reduce the incidence of inflammation . Curcumin is also involved in other signaling pathways like it induces degranulation in human neutrophils by increasing the cell surface expression of clusters of differentiation 35 (CD35), CD66b, and CD63 .…”
Section: Introductionmentioning
confidence: 99%